Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am not sure what is going wrong here. I have been doing other applications of the chain rule to cross check that I understand it properly ,but I still do not get a correct answer on this problem while I do on all others.

$$y = (1-x^{-1})^{-1}$$

$$y' = -(1-x^{-1})^{-2} \cdot x^{-2}$$

This is wrong and it gives a wrong answer, according to wolfram and my book the answer should just be the first part which breaks the chain rule and I do understand why this is acceptable in this specific case but no others.

share|improve this question
1  
Look more closely at what Alpha gives you back - it's not quite the first half of what you've written. What you've written is actually correct, but try expanding out the result and you may see where Alpha is coming from. –  Steven Stadnicki Jan 9 '13 at 16:29
    
I have several times with no luck. –  user56699 Jan 9 '13 at 16:30
    
$$-(1-x^{-1})^{-2}x^{-2}=\frac{-1}{x^2(1-x^{-1})^2}=\frac{-1}{x^2\left(1-\frac1x‌​\right)^2}=\frac{-1}{\left(x\left(1-\frac1x\right)\right)^2}=\frac{-1}{(x-1)^2}$$ –  Brian M. Scott Jan 9 '13 at 16:33
    
@BrianM.Scott Why did the x^2 turn into just an x in the third step? –  user56699 Jan 9 '13 at 16:35
    
I don't know how you knew to use those specific and very odd manipulations but I did something more intuitive and it just doesn't work. I took $(x^{-1} - 1$ and squared it getting $x^{-2} - 2x^{-1} + 1$ which is very bad and wrong. I then multiply that by $x^2$ and get $(1-2x+x^2)^{-1}$ –  user56699 Jan 9 '13 at 16:38

4 Answers 4

up vote 2 down vote accepted

You applied the chain rule correctly, and obtained "a" correct answer; the discrepancy you find is "simply" due to the fact that your answer can be simplified. (No pun intended!)

Expanding your correct result: $\;\;y' = -(1-x^{-1})^{-2}x^{-2};\;$ we simplify as follows: $$=\frac{-1}{x^2(1-x^{-1})^2}\tag{1}$$ $$=\frac{-1}{x^2\left(1-\frac1x‌​\right)^2}\tag{2}$$ $$=\frac{-1}{\left(x\left(1-\frac1x\right)\right)^2}\tag{3}$$ $$=\frac{-1}{(x-1)^2}\tag{4}$$ $$= -(x-1)^{-2}\tag{5}$$


So your computation/answer is equivalent to $(5)$.


Note: $(2) \to (3)\;\;$ uses the fact that $\;x^ny^n = (xy)^n,\;\text{so}\; (2)$ is equivalent to $(3)$

share|improve this answer

There is a neater way of handling this. Denote $\log f(x)=Lf(x)$.

$$ f(x)=\bigg(1-\frac{1}{x}\bigg)^{-1}\\ Lf(x)=- \log \bigg(1-\frac{1}{x}\bigg)=\log x -\log (x-1)\\ L'f(x)=\frac{1}{x}-\frac{1}{x-1}=-\frac{1}{x(x-1)}\\ f'(x)=-\frac{f(x)}{x(x-1)}=-\frac{1}{(x-1)^2} $$

EDIT: here I used the following properties of logarithm function: $$ \log \frac{f(x)}{h(x)}=\log f(x)-\log h(x)\\ \textbf{ If } g(x)=\log f(x) \textbf{ then } \\ g'(x)=\frac{f'(x)}{f(x)} \Leftrightarrow \\ f'(x)=f(x)g'(x) $$

share|improve this answer
2  
I have no idea why you introduced logs into this, what L means, what L! is or really anything that you did. It might be neater but I don't think it is anything we were ever taught. –  user56699 Jan 9 '13 at 16:39
    
Pls see edits above –  Alex Jan 9 '13 at 16:44
    
I really can't decipher what you wrote at all. I think you wrote teh chain rule out maybe and you are saying that you took the logs of both sides but I am not sure when or how they went away. –  user56699 Jan 9 '13 at 16:49
    
I didn't use Chain rule here because it is not the only way of solving this problem. Yes, I took logs of both sides and then differentiated the function:$(\log x)'_{x}=\frac{1}{x}$ –  Alex Jan 9 '13 at 16:51
    
I am not familiar with that at all don't you have to raise everything to e or something like that to get rid of log? –  user56699 Jan 9 '13 at 17:08

Set $f(x)=u^{-1}$ wherein $u=1-\frac{1}{x}$. So according to chain rule we have: $$\frac{df(x)}{dx}=\frac{df}{du}\cdot\frac{du}{dx}$$ Here, $$\frac{df}{du}=-1\times u^{-1-1}=-u^{-2}$$ and $$\frac{du}{dx}=-(x^{-1})'=x^{-2}$$ So you have your answer.

share|improve this answer
    
+1 Nice...I remember this problem ;-) –  amWhy Feb 20 '13 at 0:28

No, you're right. You just expressed it a little diffently. Remember that $a^xb^x=(ab)^x$

$-(1-x^{-1})^{-2}x^{-2}=-((1-x^{-1})x)^{-2}=-(x-1)^{-2}=-\frac{1}{(x-1)^2}$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.